KUAT TEKAN BETON ROLLER COMPACTED CONCRETE (RCC)-FLY ASH 15% YANG DIRENDAM SODIUM SULFAT - Jodiansyah; Sulistyorini, Dewi; Gutama, Detha Sekar Langit Wahyu (KURVATEK, 2024)
RCC (Roller Compacted Concrete) pavement is known for its durability, cost-effectiveness, long lifespan, and low maintenance. In this study, RCC concrete was compacted using a vibrator hammer in three layers, each with a compaction time of 20 seconds per layer. The mix proportions were based on SNI 03-2834-2000 and modifications from several journals, with a target compressive strength of 25 MPa. The materials used included coarse aggregate, fine aggregate, Portland Composite Cement (PCC), water, fly ash, and superplasticizer (SPC). The percentage of fly ash used in this study was 15% of the cement weight, with a total of 12 test specimens. The compressive strength of cylindrical concrete samples with a diameter of 15 cm and a height of 30 cm was tested using two immersion variations: ordinary water and sodium sulfate (Na2SO4), and two durations: 14 days and 28 days. The results showed that the compressive strength of RCC 15 B-14 was 49.16 MPa, RCC 15 B-28 was 52.29 MPa, RCC 15 S-14 was 46.87 MPa, and RCC 15 S-28 was 50.65 MPa. Immersion in sodium sulfate for 14 days resulted in a compressive strength reduction of 4.7% compared to ordinary water immersion, while immersion in sodium sulfate for 28 days resulted in a compressive strength reduction of 3.1% compared to ordinary water immersion. However, the compressive strength results still exceeded the planned strength of 25 MPa